Training characteristics of qualifiers for the U.S. Olympic marathon trials - Karp, J. R. (International Journal of Sports Physiology and Performance, 2007)
To describe and compare training characteristics of the 2004 U.S. Olympic Marathon Trials qualifiers. Methods: All qualifiers (104 men, 151 women) received questionnaires. Ninety-three (37 men, 56 women) responded and were categorized as elite (men <2 hours 15 min, women <2 hours 40 min) or national class. Results: Men and women ran 75% and 68% of their weekly training distance, respectively, below marathon race pace. Men trained longer than women (12.2 ± 5.3 vs 8.8 ± 5.6 years), ran more often (8.7 ± 2.8 vs 7.1 ± 2.5 times/wk), and ran farther (145.3 ± 25.6 vs 116.0 ± 26.5 km/wk). Elite women ran more than national-class women (135.8 ± 31.5 vs 111.3 ± 23.3 km/wk). Distances run at specific intensities were similar between sexes. For men and women, respectively, 49% and 31% did not have a coach and 65% and 68% trained alone. Marathon performance correlated to 5-km, 10-km, and half-marathon performance and to years training, average and peak weekly distance, number of weekly runs, and number of runs ³32 km for women. Conclusions: Among U.S. Olympic Marathon Trials qualifiers, there is no consensus as to how to prepare for the marathon beyond running at a pace slower than race pace. Weekly training distance seems to influence women's marathon performance more than it does men's. Because many of these athletes train alone and without a coach, further research is warranted on the reasons that these athletes train the way they do.